Isaac Jaquelot on the preeminence of physico-theology - Adam Drozdek (Warszawskie Studia Teologiczne)
Isaac Jaquelot was a seventeenth-century ecclesiastic concerned about the rising tide of deism and atheism. In his theological treatises he wanted to prove, among others, the existence of God, the fact that God is a spiritual being, and that He created the world as described in the Tora. In his proofs, he relied very strongly on empirical approach and human rationality recognizing the limitation of the human reason. In this, he promoted physico-theology as the most viable approach to be used.